A proposal for the revision of student personnel services of the Bicol University - Ojano, Esperanza Tanael 1926- (1977)
This is a proposal for the revision of the existing student personnel services of the Bicol University. The purposes of the study were: to explore the needs of the students of the Bicol University, to find out which among the existing services needed revision, and to propose a revision of the existing services if data would support the need for a revision. The study made use of the Limcaco questionnaire, modified questionnaires, interviews and documentary analysis. Findings revealed that the student personnel services did not approximate an ideal set-up of student personnel services. Problems in organization and implementation of services existed in all the different student personnel offices. Most of the offices are not coordinated by the Office of Student Affairs.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Bicol University; Personnel service in higher education -- Philippines -- Bicol